The impact of climate change the Himalayas (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Climate change is a very significant issue, and it is a matter that requires serious contemplation. The Himalayas, a crucial component of Earth’s, ecosystems are facing numerous problems and dangerous due to climate change. For example rising temperatures, changing rainfall patterns and altered weather conditions. All these factors are causing changes in the Himalayan ecosystems . These points highlight the destructive effects of climate change on the Himalayas. This report highlight the including glacier retreat water security food security are increased risk of natural disaster. The consequences of climate change are far-reaching, affecting not only the Environment but also human settlements. Urgent action is needed to mitigate the impacts of climate change a d promote sustainable Development in the Himalayan.